A Fatal Twist: Volvulus of the Small Intestine in a 46-Year-Old Woman. (3rd November 2015) - Klein, Jared; Baxstrom, Kathryn; Donnelly, Stephen; Feasel, Patrick; Koles, Paul
Abstract : A 46-year-old woman presented to two emergency departments within 12 hours because of acute abdominal pain. Physical exam demonstrated tenderness and epigastric guarding. An ultrasound was interpreted as negative; she was discharged home. Later that evening, she was found dead. Postmortem exam revealed acute hemorrhagic necrosis of a segment of jejunum secondary to volvulus. Clinical clues suggesting presentations of small bowel volvulus are usually nonspecific; the diagnosis is typically confirmed at surgery. Her unremitting abdominal pain, persistent vomiting, and absolute neutrophilia were consistent with an acute process. The etiology of this volvulus was caused by an elastic fibrous band at the root of the jejunal mesentery. While congenital fibrous bands are rare in adults, this interpretation is favored for two reasons. First, the band was located 20 cm superior to postsurgical adhesions in the lower abdomen and pelvis. Second, there was no history of trauma or previous surgery involving the site of volvulus.